Practical Recommendations on Supplemental Feeding Introduction - S. G. Makarova (Union of pediatricians of Russia, 2016)
Despite the availability of a national consensus document describing in detail modern approaches to feeding infants, pediatricians keep on giving most diverse recommendations on the time of supplemental feeding introduction. The article presents a brief historical review, as well the modern view on the issue of introduction of supplemental feeding to children. In the previous century, it was common both in Russia and most European countries to introduce supplemental feeding to children at the age of 2 or even 1.5 months. In 2002, the World Health Organization put forward an initiative in support of breastfeeding and recommended not to introduce supplemental feeding before the age of 6 months. A certain "golden mean" has apparently been achieved on the basis of results of studies and a longterm discussion among the specialists in feeding from different countries - all scientific communities and national recommendations of most countries define the optimal age for supplemental feeding introduction as "from 4 (completed) months to 6 (completed) months" with certain individual approach.